2016
DOI: 10.1002/pmh.1332
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood and predictors of detention in patients with personality disorder compared with other mental disorders: A retrospective, quantitative study of Mental Health Act assessments

Abstract: Detention rates in patients with personality disorder are lower than those for other disorders but are still substantial. Risk factors for detention in patients with personality disorder differ from those with other mental disorders. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Nine studies found that suicidal behaviour, ideation, and history were associated with voluntary rather than involuntary hospitali sati on. 17,27,28,43,67,80,82,85,86 In five studies, risk to self was associated with involuntary admission, 7,69,72,74,87 whereas in 17 studies, no association was noted between risk to self and the legal status of admission. 30,34,38,41,42,58,59,71,73,75,77,79,89,91,92,95,96 18 studies reported on risk to others and all noted a positive association with involuntary hospitalisation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Nine studies found that suicidal behaviour, ideation, and history were associated with voluntary rather than involuntary hospitali sati on. 17,27,28,43,67,80,82,85,86 In five studies, risk to self was associated with involuntary admission, 7,69,72,74,87 whereas in 17 studies, no association was noted between risk to self and the legal status of admission. 30,34,38,41,42,58,59,71,73,75,77,79,89,91,92,95,96 18 studies reported on risk to others and all noted a positive association with involuntary hospitalisation.…”
Section: Resultsmentioning
confidence: 97%
“…30,34,38,41,42,58,59,71,73,75,77,79,89,91,92,95,96 18 studies reported on risk to others and all noted a positive association with involuntary hospitalisation. 7,17,30,34,41,43,[58][59][60]67,69,[72][73][74]79,80,91,95 However, measurement and definition of risk to others was inconsistent throughout these studies, with scant use of formal assessment scales. Three studies used HONOS to record levels of aggression, 58,59,91 two used the Overt Aggression Scale, 17,73 two used the Risk of Harm to Others Scale, 7,69 two used an item of the Personal and Social Performance scale (disturbing and aggressive behaviour, 41 and danger to others).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies captured data on individuals having received care in the public hospital system but excluded the least impaired cases (eg, those having received care in the private sector) and the most severely impaired cases (eg, those who ended up in detention without receiving care). 22 It is important to note that these studies highlight the diminishing reluctance of clinicians to diagnose BPD in adolescents, since the work was based on diagnostic data recorded by the adolescent’s treating physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies along the same lines as Hossain et al 1 should also examine the proportion of people admitted with personality disorder under the Mental Health Act. Those with personality disorder are sectioned less often after formal assessment than those with other diagnoses, but at 41% the proportion is still substantial 14 and may be increasing. This certainly appears to be the case in those with personality dysfunction and intellectual disability 15 and is a matter of some concern, as in this population the diagnosis of personality disorder is more contentious.…”
mentioning
confidence: 99%